The Rough guide to Japan. - Richmond, Simon, ....-; Dodd, Jan, ....- (London : Rough Guides, 2011)
The award-winning Rough Guide to Japan is the definitive guide to this fascinating country with its stunning landscapes, dynamic pop culture, world-class dining and rich history. It will guide you with reliable information and a clearly explained background on everything from Japan's history, religions, arts, movies and music to the country's pressing environmental issues. Whether you're looking for great places to eat and drink or the most exciting places to party and the newest accommodation, you'll find the solution. Plus, all the major and many off-the-beaten-track sights are covered, including tropical dives in Okinawa, mountain traverses across the Japanese Alps and contemporary art exhibits on islands in the Inland Sea. Accurate maps and comprehensive practical information help you get under the skin of this dynamic country, whilst stunning photography and a full-colour introduction make The Rough Guide to Japan your ultimate travelling companion.
Keywords: Japan -- Reisgidsen